Promoting knowledge of sexual illnesses among women in Bangladesh: Can non-governmental organizations play a role? - Abdullahel Hadi; Roxana Parveen (Asia-Pacific Population Journal, 2003)
The sexually transmitted infections (STIs) are significant causes of morbidity and mortality among women of reproductive age. Not only do some of the STI-related complications result in spontaneous abortion, infertility, ectopic pregnancy and cervical cancer, but common STIs can also cause long-term impairment of reproductive health and in crease the risk of HIV transmission from one person to another (Cameron, Simonsen and D’Costa, 1989; Wasserheit, 1992; Population In formation Program, 1993). It has been estimated that sexually transmitted infections and their complications collectively rank second in importance in the world among diseases in women of reproductive age (World Bank, 1993). Ignorance of and misinformation on sexual illnesses are of ten considered power fulbarriers to resolving such health problems in the traditional communities (UNAIDS, 1998).